The Copenhagen soccer test: physiological response and fatigue development - Bendiksen, M.; Bischoff, R.; Randers, M. B.; Mohr, M.; Rollo, I.; Sueta, C.; Bangsbo, J.; Krustrup, P. (Medicine & Science in Sports & Exercise, 2012)
Introduction: The aims of the study were 1) to evaluate whether a multifaceted simulated soccer game protocol, entitled the Copenhagen Soccer Test (CST), elicited a similar physiological loading as a competitive game (CG) and 2) to determine muscle metabolites, blood variables, and sprint performance in various phases of CST.